PENGARUH KEPERCAYAAN, KEMUDAHAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU CONVERSE DI E-COMMERCE SHOPEE - Ananda Miftahul Alfikri; Kuwat Riyanto (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to determine the effect of trust, convenience and product perceptions on purchasing decisions with a sample of 100 respondents. The method used in this research is a quantitative research method with the additional method of using the SmartPLS 2023 application. The results of this study show that trust has a significant influence on purchasing decisions for Converse shoe products, so that it is in accordance with the first hypothesis. This also indicates that the existence of trust from consumers will be able to increase the purchasing decision of Converse shoe products, that convenience has a significant influence on the purchase decision of Converse shoes, so that it is in accordance with the second hypothesis. This also indicates that the easier it is to buy Converse shoe products, the higher the decision to buy Converse shoes and that the perceived price has a significant influence on the decision to buy Converse shoes, so that is in accordance with the third hypothesis. This also indicates that an affordable price will be able to increase the decision to buy Converse shoes. Keywords: Trust, Convenience and Purchase Decision.